It Takes a Village to Grow a Person: A Case of a Psychoanalytic Treatment in a Hospital Setting. Issue 1 (1st January 2019) - Kolano, Megan M.
ABSTRACT: In today's culture of evidence-based treatment and managed care, psychoanalysis is mostly relegated to the private consulting rooms of psychoanalysts, no longer available in hospital settings for those who need more containment than a single psychotherapist can offer. At the Austen Riggs Center, we work with our patients in four-times-a-week individual psychoanalytic psychotherapy and use psychoanalytic ideas about groups and their processes to understand the individual's role in social context, particularly within their family system. Working psychoanalytically within a larger system raises interesting questions about the role and nature of transference and countertransference when it is not solely emerging between patient and analyst, but rather with many people across situations. Whereas the consulting room remains a privileged space for the patient to work as an individual, the therapeutic community offers a different kind of consulting room, a social space where therapist or analyst also participates alongside his or her patients. Such a setting requires that one think about how to integrate experiences in the social realm into the fantasy space of psychoanalytic psychotherapy. This paper offers a window into the nuances of such a treatment in our hospital setting and illustrates the process of synthesizing the wealth of information gleaned from such an immersive treatment environment.